The unusual suppression of superconducting transition temperature in double-doping 2H-NbSe2. (5th July 2019) - Yan, Dong; Lin, Yishi; Wang, Guohua; Zhu, Zhen; Wang, Shu; Shi, Lei; He, Yuan; Li, Man-Rong; Zheng, Hao; Ma, Jie; Jia, Jinfeng; Wang, Yihua; et al.
Abstract: 2H-NbSe2 is one of the most widely researched transition metal dichalcogenide (TMD) superconductors, which undergoes charge-density wave (CDW) transition at T CDW about 33 K and superconducting transition at T c of 7.3 K. To explore the relation between its superconductivity and Fermi surface nesting, we have combined S substitution with Cu intercalation in 2H-NbSe2 to make Cu x NbSe2− y S y (0 ≤ x = y ≤ 0.1). Upon systematic substitution of S and intercalation of Cu ions into 2H-NbSe2, we found that when the Cu and S contents ( x = y ≥ 0.06) increase, the T c decreases in Cu x NbSe2− y S y . At higher x and y values, T c keeps a constant value near 2 K, which is not commonly observed for a layered TMD. For comparison, we found that the simultaneous substitution of Nb by Cu and Se by S in Cu x Nb1− x Se2− y S y (0 ≤ x = y ≤ 0.06) lowered the T c substantially faster. We constructed superconducting phase diagrams for our double-doping compounds in contrast with the related single-ion doping systems.